2023
DOI: 10.3390/polym15071749
|View full text |Cite
|
Sign up to set email alerts
|

ZnO NRs/rGO Photocatalyst in a Polymer-Based Microfluidic Platform

Abstract: This paper reports the development of ZnO NRs/rGO-based photocatalysts integrated into a tree-branched polymer-based microfluidic reactor for efficient photodegradation of water contaminants. The reactor system includes a photocatalytic reactor, tree-branched microfluidic channels, and ZnO nanorods (NRs) coated with reduced graphene oxide (rGO) on a glass substrate within an area of 0.6 × 0.6 cm2. The ZnO NRs/rGO acts as a photocatalyst layer grown hydrothermally and then spray-coated with rGO. The microfluidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Based on this simulation study, as the flow rate varies with respect to velocity, the pressure drop in the fluid flow system depends on the resistance to flow. Finally, it has been found from eqs and that the flow rate and effective residence time became 1.75 × 10 –6 m 3 /s and 0.033 s, respectively . The purpose of this fluid flow impacts the growth and behavior of cells within a biological or bioprocess system.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Based on this simulation study, as the flow rate varies with respect to velocity, the pressure drop in the fluid flow system depends on the resistance to flow. Finally, it has been found from eqs and that the flow rate and effective residence time became 1.75 × 10 –6 m 3 /s and 0.033 s, respectively . The purpose of this fluid flow impacts the growth and behavior of cells within a biological or bioprocess system.…”
Section: Resultsmentioning
confidence: 94%
“…The flow rate ( Q ) for the rectangular channel and effective residence time ( t R ) were calculated using eqs and where v is the fluid velocity and A is the cross-sectional area of the microfluidic flow. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research implementing a microfluidic platform has shown that higher degradation of dye using photocatalysts can be achieved, as the nanostructured photocatalyst is brought into very close proximity to the water flow channel [154].…”
Section: Catalyst Loading and Reactor Designmentioning
confidence: 99%